PID CONTROLLER TUNED BY METAHEURISTIC ALGORITHM USING ANT LION OPTIMIZER FOR VIBRATION CONTROL OF HORIZONTAL FLEXIBLE STRUCTURE (Jurnal Mekanikal, 2026)
applications, including aerospace, robotics, and precision machinery. Passive vibration control approaches are effective for high-frequency applications, but often fail against low-frequency vibrations. Hence, active vibration control (AVC) is introduced to address this limitation. Among various AVC techniques, PID controller remains one of the most widely adopted methods. However, optimal tuning for PID parameters remains a challenge in complex dynamic systems. Thereore, this study explores the application of ant lion optimizer (ALO) to fine-tune PID parameters for vibration cancellation in a flexible structure. The optimization process is based on single objective function by minimizing the mean square error (MSE). Inspired by the predatory behaviour of antlions, ALO iteratively adjusts kp, ki, and kd values by updating the position of ants and antlions based on fitness evaluations. The performance of the PID-ALO controller is validated through MATLAB/ Simulink R2021a by assessing its effectiveness in attenuating vibrations induced by single and multiple sinusoidal disturbances. Results indicate that the PID-ALO controller outperformed the classical PID-ZN controller by achieving an attenuation level of 47.45 dB with 45.85% vibration reduction under single sinusoidal and 46.97 dB with 40.04% reduction under multiple sinusoidal disturbances. These findings highlight the potential of ALO in precise PID tuning, representing the first implementation of a PID-ALO controller on a horizontal flexible plate under dual excitation disturbances.
Keywords: active vibration control; Ant lion optimizer; flexible structure; Metaheuristic algorithm; PID controller